Borrowed Reserves and Bank Expansion - Bradford, Frederick A. (Quarterly Journal of Economics, 1928)
Journal Article Borrowed Reserves and Bank Expansion Get access Frederick A. Bradford Frederick A. Bradford Lehigh University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 43, Issue 1, November 1928, Pages 179–184, https://doi.org/10.2307/1883947 Published: 01 November 1928